Programa Rede de Oportunidades: um estudo sobre as mudanças ocorridas na vida cotidiana de usuárias - Distrito de Changuinola - Provincía de Bocas Del Toro - Panamá 2006/2010 - Gracia, Gisela Aracely Barahona de (2011)
This thesis has as object, the analysis of the Program of Network of Opportunities: a study on the changes that occurred in the daily lives of the users, in the District of Changuinola- province of Bocas del Toro Panama 2006/2010. The main aim of this study was to analyze the meanings expressed by the subjects of this research in the understanding of the proposal of the program Network of Opportunities, the changes in the daily lives of the users in Changuinola and their families from the participation in this program of income transference and in their dreams and future projects. From the methodological point of view, this research is considered quant-qualitative; it allows knowing the changes in the daily life of twenty-five users that participated of the referred program. It comprised three interrelated stages: bibliographic investigation, documental investigation and field research, including the observation of the participants, semi-structural interviews, as well as video and photography. Classic and contemporary authors where chosen especially Brazilian and Latin Americans. The central conceptual references such as poverty, daily life and participation, social and citizenship inclusion/exclusion, likewise other complementary concepts as family, social politics, income transference and globalization were also taken in account. The results of this research revealed that in four years of existence of the Program of Network of Opportunities in the district of Changuinola is contributing for initial improvements in the lives of families that use the program in the areas of food, health, education, transportation and in a lesser way the material conditions of the housing and acquisition of some articles for the comfort and recreation of the family members. These improvements are usually understood as help, directed primarily towards the comprehension of the social assistant as a right, in the perspective of the construction of citizenship. In this sense, a process has also been initiated as an intercultural relation between some users of different ethnic groups (Ngöbe and Kuna), (Ngöbe and Latin) that have joined together to perform works and activities to generate income and establish communitarian relations. In addition, there are some limits within which we can mention the small number of promoters regarding the number of families; we also consider that the socio-educational work is fundamental to the success of the program As well as the need to optimize better the natural resources of the region through the articulated work in between the different institutions. We believe that to the Association of Social Workers of Panama, corresponds the challenge to fight for the creation of a specific law of Social Assistance in the Republic of Panama